Spot the plot : a riddle book of book riddles - Lewis, J. Patrick (Chronicle Books, 2009)
Thirteen witty and wacky poems pose riddles that challenge readers to "Name That Book." With a glass slipper here and a spiderweb there, Lynn Munsinger's adorable illustrations lead young readers to the solutions. From Goodnight Moon to Madeline, children and parents alike will delight in recognizing their most cherished stories.